Structural significance of an evaporite formation with lateral stratigraphic heterogeneities (Southeastern Pyrenean Basin, NE Spain). (September 2017) - Carrillo, Emilio; Koyi, Hemin A.; Nilfouroushan, Faramarz
Abstract: We run a series of analogue models to study the effect of stratigraphic heterogeneities of an evaporite formation on thin-skinned deformation of the Southeastern Pyrenean Basin (SPB; NE Spain). This basin is characterized by the existence of evaporites, deposited during the Early-Middle Eocene with lateral variations in thickness and lithological composition. These evaporites are distributed in three lithostratigraphic units, known as Serrat Evaporites, Vallfogona and Beuda Gypsum formations and acted as décollement levels, during compressional deformation in the Lutetian. In addition to analogue modeling, we have used field data, detailed geological mapping and key cross-sections supported by seismic and well data to build a new structural interpretation for the SPB. In this interpretation, it is recognized that the basal and upper parts of the Serrat Evaporites acted as the main décollement levels of the so-called Cadí thrust sheet and Serrat unit. A balanced restoration of the basin indicates that thrust faults nucleated at the stratigraphic transition of the Serrat Evaporites (zone with lateral variations of thickness and lithological composition), characterized by a wedge of anhydrite and shale. The analogue models were setup based on information extracted from cross-sections, built in two sectors with different lithology and stratigraphy of the evaporites, and the restored section of the SPB. In these models, deformation preferentially concentrated in areas where thickness change, defined by wedges of the ductile materials, was inbuilt. Based on the structural interpretation and model results, a kinematic evolution of the SPB is proposed. The kinematic model is characterized by the generation of out-of-sequence structures developed due to lateral stratigraphic variations of the Serrat Evaporites. The present work shows a good example of the role of stratigraphic heterogeneities of an evaporite formation which acts as décollement level on structural deformation in a fold-thrust belt. The results of this work have implications for hydrocarbon exploration and are relevant for studying structural geometry and mechanics in shortened evaporite basins. Highlights: The effect of stratigraphic heterogeneities of an evaporite formation on thin-skinned deformation is studied. A structural re-interpretation and a kinematic evolution of the Southeastern Pyrenean basin are presented. Deformation is influenced by lateral stratigraphic heterogeneities in an evaporite formation. Implications for hydrocarbon exploration in the Southeastern Pyrenean basin.